Multilayer stag beetle elytra perform better under external loading via non-symmetric bending properties. Issue 144 (25th July 2018) - Kundanati, Lakshminath; Signetti, Stefano; Gupta, Himadri S.; Menegon, Michele; Pugno, Nicola M.
Abstract : Insect cuticle has drawn a lot of attention from engineers because of its multifunctional role in the life of insects. Some of these cuticles have an optimal combination of lightweight and good mechanical properties, and have inspired the design of composites with novel microstructures. Among these, beetle elytra have been explored extensively for their multilayered structure, multifunctional roles and mechanical properties. In this study, we investigated the bending properties of elytra by simulating their natural loading condition and comparing it with other loading configurations. Further, we examined the properties of their constitutive bulk layers to understand the contribution of each one to the overall mechanical behaviour. Our results showed that elytra are graded, multilayered composite structures that perform better in natural loading direction in terms of both flexural modulus and strength which is likely an adaptation to withstand loads encountered in the habitat. Experiments are supported by analytical calculations and finite element method modelling, which highlighted the additional role of the relatively stiff external exocuticle and of the flexible thin bottom layer in enhancing flexural mechanical properties. Such studies contribute to the knowledge of the mechanical behaviour of this natural composite material and to the development of novel bioinspired multifunctional composites and for optimized armours.